Idaho Contest party sent by the Idaho Falls Post, Alaska Yukon Pacific Exposition, Seattle, July 5, 1909. - Nowell, Frank H., 1864-1950 (1909)
On verso of image: Idaho Contest girls Caption on image: x2382 PH Coll 727.412 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number